2023
DOI: 10.1200/jco.2023.41.36_suppl.405736
|View full text |Cite
|
Sign up to set email alerts
|

Zolbetuximab + CAPOX in 1L claudin-18.2+ (CLDN18.2+)/HER2− locally advanced (LA) or metastatic gastric or gastroesophageal junction (mG/GEJ) adenocarcinoma: Primary phase 3 results from GLOW.

Abstract: 405736 Background: There is an unmet need for novel targeted therapies that improve outcomes for pts with HER2− LA unresectable or mG/GEJ adenocarcinoma. CLDN18.2 is expressed in normal gastric mucosa cells and retained in most G/GEJ adenocarcinomas. In the phase 3 SPOTLIGHT study, zolbetuximab, a CLDN18.2-targeted chimeric monoclonal antibody, significantly prolonged PFS and OS in pts with CLDN18.2+/HER2− LA unresectable or mG/GEJ adenocarcinoma when combined with mFOLFOX6. GLOW (NCT03653507) is a phase 3 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…A survival benefit was also demonstrated in the investigational group with a significant reduction in the risk of death vs. placebo (HR: 0.75; 95% CI: 0.60–0.94; P=0.0053) ( 56 ). Similar results were replicated in the GLOW trial, a global, randomized, placebo-controlled, double-blind, phase 3 trial ( 57 ). Here, CAPOX was used instead of mFOLFOX6.…”
Section: Claudin-18 Isoform 2 (Cldn182)mentioning
confidence: 53%
See 2 more Smart Citations
“…A survival benefit was also demonstrated in the investigational group with a significant reduction in the risk of death vs. placebo (HR: 0.75; 95% CI: 0.60–0.94; P=0.0053) ( 56 ). Similar results were replicated in the GLOW trial, a global, randomized, placebo-controlled, double-blind, phase 3 trial ( 57 ). Here, CAPOX was used instead of mFOLFOX6.…”
Section: Claudin-18 Isoform 2 (Cldn182)mentioning
confidence: 53%
“…Here, CAPOX was used instead of mFOLFOX6. Both mOS (14.39 vs. 12.16 months; HR: 0.771; P=0.0118) and mPFS (8.21 vs. 6.80 months; HR: 0.687; P=0.0007) were found to be significantly prolonged with zolbetuximab compared to placebo ( 57 ). Of note, CLDN18.2-positivity was fairly common, seen in 40% of screened patients in both trials ( 56 , 57 ).…”
Section: Claudin-18 Isoform 2 (Cldn182)mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results from the GLOW trial have validated the results of the SPOTLIGHT trial [111]. This trial found that zolbetuximab in combination with capecitabine and oxaliplatin (CAPOX) extended OS in patients with unresectable locally advanced or metastatic CLDN 18.2+ GC compared to placebo and CAPOX (14.4 versus 12.2 months, HR = 0.771, p = 0.0118) [111].…”
Section: Claudin 182: a Newer Gc Targetmentioning
confidence: 90%
“…Zolbetuximab is a first-in-class monoclonal antibody that binds to the protein claudin 18.2. Targeting this protein has demonstrated promising results in HER2-negative patients, as observed in the clinical trials SPOTLIGHT (NCT03504397) [134] and GLOW (NCT03653507) [135], in which Zolbetuximab was tested in association with first-line chemotherapy. The ongoing ILUS-TRO trial will provide information in pre-treated HER2-positive gastric cancer patients, with results still pending.…”
Section: Second and Further Linesmentioning
confidence: 99%